Efficacy and safety of oral mifepristone for cervical priming and induction of labor in term pregnancy - Gupta, Abhilasha; Verma, Aruna; Madan, Iti; Kashyap, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objectives of the study was to assess the efficacy of mifepristone in priming the cervix/inducing labor over next 96 hrs in term pregnancy. Methods: In this single blind randomized controlled trial 200 women with term pregnancy beyond 39 weeks and Bishop’ score <6 were randomly allocated into two groups. Tab Mifepristone 400 mg orally was given to women in study group (n=100) and no intervention in control group (n=100). On follow up one case was lost in control group. All women were observed for change in the bishop’s score or onset of labor in next 96 hrs. If Bishop’s score was <6, the choice of induction was left on the clinician/patient. Results: Mean induction to delivery interval, duration of active phase and improved Bishop score were 79.35±53.43 hr, 2.47±1.23 hr, 6.68±1.69 for study group versus 148±65.66 hr, 3.09±1.45 hr, 5.8±2.15 for control group (p value is <0.001) respectively. Seventy one (71%) women in study group and 39 (39.3%) women in control group delivered vaginally within 96 hrs without any need of augmentation. There were 9 (9%) caesareans in study group and 24 (24.2%) caesareans in control group but no instrumental delivery in both groups. There was no statistically difference in perinatal outcomes between two groups. Conclusions: Mifepristone is an effective drug for cervical ripening and initiation of labor when given in term pregnancy beyond 39 weeks with poor Bishop’s score (<6) and appearing to reduce need for other agent for augmentation of labor.